Interactions involving intestinal nematodes of rodents: experimental and field studies - Behnke, J.M.; Bajer, A.; Sinski, E.; Wakelin, D. (Cambridge University Press, 2001)
Multiple species infections with parasitic helminths, including nematodes, are common in wild rodent populations. In this paper we first define different types of associations and review experimental evidence for different categories of interactions. We conclude that whilst laboratory experiments have demonstrated unequivocally that both synergistic and antagonistic interactions involving nematodes exist, field work utilizing wild rodents has generally led to the conclusion that interactions between nematode species play no, or at most a minor, role in shaping helminth component communities. Nevertheless, we emphasize that analysis of interactions between parasites in laboratory systems has been fruitful, has made a fundamental contribution to our understanding of the mechanisms underlying host-protective intestinal immune responses,and has provided a rationale for studies on polyparasitism in human beings and domestic animals. Finally, we consider the practical implications for transmission of zoonotic diseases to human communities and to their domestic animals, and we identify the questions that merit research priority.